Quantification of TGF-ß1, PDGF and IGF-1 cytokine expression after fracture treatment vs. non-union therapy via masquelet. Issue 2 (February 2016) - Fischer, Christian; Doll, Julian; Tanner, Michael; Bruckner, Thomas; Zimmermann, Gerald; Helbig, Lars; Biglari, Bahram; Schmidmaier, Gerhard; Moghaddam, Arash
Abstract: Introduction: Biochemical processes during bone regeneration can be analysed via quantification of peripheral serum cytokine levels. To date, serum levels of cytokines in patients treated with masquelet technique and patients with normal bone healing have not been compared. This comparison is supposed to deliver novel insights into the process of bone regeneration. Our aim was to validate this established method in the monitoring of bone regeneration after non-union treatment in masquelet technique. Materials and methods: Between 04/2008 and 01/2014 three groups were recruited: G1 (10 patients) with long bone non-unions, treated successfully with masquelet therapy, G2 (6 patients) with unsuccessful masquelet therapy and G3 (10 patients) with long bone fractures and normal bone healing. Peripheral blood samples were collected over a period of six months following a standardised time pattern in combination with clinical and radiologic follow up. TGF-ß1, PDGF-AB and IGF-1 were measured using commercially available immunoassays. Results: TGF-ß1 levels in G1 and G2 demonstrated a parallel and lower overall concentration over time compared to G3. G3 showed a significant TGF-ß1 peak 2 weeks after surgery compared to G1 ( p  = 0.0054). PDGF-AB concentrations were always lower in G2 than in G1 and G3. G3 peaked at week 2 with a significant higher value than in G2 ( p  = 0.0177). IGF-1 showed lower overall serum concentrations in G2 than in G1 and G3. G1 had a peak level during the fourth week of follow-up. Compared to G2 this peak was significant ( p  = 0.0015). Conclusions: This study shows that successful bone regeneration via masquelet technique only partially imitates cytokine expression of physiological bone healing. High expressions of IGF-1 correspond to a successful masquelet therapy while TGF-ß seems to play a minor role. These results assume that objective analysis of an effective non-union therapy with cytokine expression analysis is possible even with a small number of patients.